Analisis Kesulitan Belajar Siswa dalam Memahami Operasi Penjumlahan Bilangan Bulat di Kelas VI SDN 1 Kersanagara - Kania Kencana Dewi; Geri Syahril Sidik; Riza Fatimah Zahra (Journal Innovation In Education, 2024)
Mathematics learning, particularly in the area of integer addition operations, remains difficult for students to understand. This study aims to analyze the learning difficulties students face in understanding integer addition operations in the sixth grade at SDN 1 Kersanagara. Using a descriptive qualitative approach, this research explains the students' difficulties without manipulating variables. Data were collected through direct interviews and written tests. The descriptive approach was chosen to obtain detailed information about the students' difficulties with integer addition operations. Data were gathered through observations, interviews, and written tests, with the research population consisting of 20 sixth-grade students at SDN Kersanagara 1. The study's results indicate that learning difficulties in mathematics, specifically in integer addition operations, are characterized by an inability to master the material within the allotted time, low academic performance, achievements not matching the students' abilities, and poor behavior such as lack of politeness and defiance. Internal factors such as physical condition, psychological state, and fatigue affect learning difficulties, while external factors are not significant as only three students experienced these difficulties.